2005
DOI: 10.1017/s0024282905014933
|View full text |Cite
|
Sign up to set email alerts
|

Manganese as a site factor for epiphytic lichens

Abstract: Decreasing abundance of epiphytic lichens with increasing Mn supply from the substratum or from stemflow was found in several coniferous forests of Europe (Germany) as well as western (Montana, British Columbia) and eastern North America (New York State). Experiments carried out with Hypogymnia physodes and other species of chloro- and cyano-lichens suggest that these correlations are causal. High Mn concentrations e.g. reduce chlorophyll concentrations, chlorophyll fluorescence and degrade the chloroplast in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 193 publications
0
36
0
Order By: Relevance
“…Mikhailova (2007) found that Cu pollution caused growth abnormalities, distortion of apothecia and colour changes in thalli of Tuckermanopsis sepincola and decreased production of soredia in Hypogymnia physodes. Excess Mn caused ultrastructural damage and inhibited soredial growth in Hypogymnia physodes (Hauck and Paul 2005).…”
Section: Accumulation Of Heavy Metals By Lichensmentioning
confidence: 99%
“…Mikhailova (2007) found that Cu pollution caused growth abnormalities, distortion of apothecia and colour changes in thalli of Tuckermanopsis sepincola and decreased production of soredia in Hypogymnia physodes. Excess Mn caused ultrastructural damage and inhibited soredial growth in Hypogymnia physodes (Hauck and Paul 2005).…”
Section: Accumulation Of Heavy Metals By Lichensmentioning
confidence: 99%
“…A largely natural chemical site factor that has been figured out to be significant for epiphytic lichens in the recent past is the local Mn supply (Hauck and Paul, 2005). Trees deposit surplus amounts of Mn in the bark (Fink, 1999;Schmull and Hauck, 2003), after the metal has been taken up from the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of field studies and experimental work showed that epiphytic chlorolichen abundance in coniferous forests of Europe and North America is, among other factors, controlled by the supply with Mn (Hauck, 2003;Hauck and Paul, 2005). Cover of many lichen species decreased with increasing Mn concentration in bark (Hauck et al, 2001;Schmull and Hauck, 2003) or stemflow (Hauck et al, 2002a;Schmull et al, 2002).…”
Section: Introductionmentioning
confidence: 99%